Factors That Affect Employee Satisfaction of Rsi Sultan Agung Banjarbaru South Kalimantan - Dewi Ariefahnoor; Ridha Setina Arini (Lembaga Pengembangan Kinerja Dosen, 2025)
With high work morale, it will create outstanding employees where work can be completed quickly, absenteeism can be minimized, damage can be reduced and the possibility of employee transfer to another company can be minimized. Work morale and job satisfaction greatly affect the achievement of company goals. If in a company the level of work morale and productivity is low, the company will experience many difficulties and even the company can go out of business if it is not dealt with immediately. RSI Sultan Agung which reads